A polymorphism in ACE2 is associated with a lower risk for fatal cardiovascular events in females: the MORGAM project - Vangjeli, Ciara; Dicker, Patrick; Tregouet, David-Alexandre; Shields, Denis C.; Evans, Alun; Stanton, Alice V.; MORGAM Project (Journal of the Renin-Angiotensin-Aldosterone System, 2011)
Angiotensin II, a vasoconstrictor and the main effector molecule of the renin–angiotensin system, is known to influence inflammation, thrombosis, low-density lipoprotein oxidation and growth factors, all of which contribute to cardiovascular disease. The associations of polymorphisms in the angiotensin-converting enzyme 2 (ACE2) gene with cardiovascular risk have not been fully determined. Single nucleotide polymorphisms (SNPs) in ACE2 were genotyped in participants of the prospective MORGAM study (n = 5092) from five cohorts: ATBC, FINRISK, Northern Sweden, PRIME/Belfast and PRIME/France. Using a case-cohort design, associations were sought between SNPs and haplotypes with cardiovascular events during follow-up (Cox proportional hazards model). The comparison group were a subset of all MORGAM participants who were selected to ensure similar age and sex distributions among the cases and controls. The A allele of the rs2285666 SNP (HR = 0.3, p = 0.04) was significantly associated with the risk of cardiovascular death in female subjects. These findings complement those found in other studies of SNPs in the ACE2 gene in relation to cardiovascular disease risk. As females carry two copies of the ACE2 gene, and given its plausible biological role in cardiovascular disease risk, further studies of ACE2 should be prioritised.